Gamification and Flipped Classroom Research: A Bibliometric Analysis of Trends of Scopus-Indexed Publications - Candra Tri Utami; Ilham Wahyudi; Aan Yuliyanto; Gibraltar Arindra Putra; Sadun Akbar (Jurnal Pendidikan Progresif, 2026)
This study examined 325 scientific articles from Scopus on gamification research within flipped classroom and technology-enhanced learning contexts. The study aimed to identify publication trends, research productivity, and emerging thematic patterns in this field. Bibliometric analysis and systematic mapping are lacking, making it difficult to understand research trends, collaboration patterns, and key themes. A bibliometric approach was employed to map trends in scientific publications. Data were collected using the Scopus database, applying Boolean operators. The selection criteria included questions about elementary, middle, and high school students and publications published between 2014 and 2024. Data analysis was carried out using VOSviewer and Bibliometrix. The findings revealed a clear increase in global research activity, with substantial growth in annual publication output. Keyword analysis revealed six interrelated research trends: New Ways of Teaching, Psychological Dimensions and Learner Engagement, Technology Drivers and Digital Environments, Implementation Context: Learning Environment and Curriculum, Evaluation of Goals and Developing Competencies, and Methods for Studies in Education. Gamification literature grew by 169 papers between 2014 and 2021. Although productivity grew between 2021 and 2024, the total number of papers was 156. This study shows that pedagogy, psychology, and technology are interconnected. It can help teachers and policymakers use gamification and AI- and Virtual Reality-enhanced teaching methods. This study emphasizes the integration of pedagogy, psychology, and technology in a comprehensive bibliometric analysis. The findings can help educators and policymakers develop new pedagogical methods, particularly using Artificial Intelligence and VR. Keywords: bibliometric analysis, flipped classroom, digital learning, gamification, and innovative classroom.